SOFTWARE ANALYSIS OF AN AUTOMATED HYDROPONICS SYSTEM - Boboyorov Azizjan Eshmuminovich; Abdurashidov Firdaus Namoz o’g’li; Aliyev Olmos Vali o’g’li (International Journal on Integrated Education, 2023)
This article automated of hydroponics software supply done increase methods present is enough Today's in the day in the world to food has been Demand increased is going Hence hydroponics _ system software supply work out of farming new stable method and market economy we will develop . "FX3U-64MT/ESS MITSUBISHI" controllers using software software supply work exit and to him need has been components in choosing Demand from being done come came out without selected sensors parameters learning and him observation and again work for software supply done increase need _ Hydroponics to systems circle previous done affairs according to inspection seeing released _ And finally gx developer software from supply used without of users mutually effect ease for one how much affairs done increased _